Spatial distribution of insecticide resistant populations of Aedes aegypti and Ae. albopictus and first detection of V410L mutation in Ae. aegypti from Cameroon - Matthew Montgomery; James F. Harwood; Aurelie P. Yougang; Theodel A. Wilson-Bahun; Armel N. Tedjou; Christophe Rostand Keumeni; Auston Marm Kilpatrick; Charles S. Wondji; Basile Kamgang (BMC, 2022)
Abstract Background Dengue (DENV), chikungunya (CHIKV) and Zika virus (ZIKV), are mosquito-borne viruses of medical importance in most tropical and subtropical regions. Vector control, primarily through insecticides, remains the primary method to prevent their transmission. Here, we evaluated insecticide resistance profiles and identified important underlying resistance mechanisms in populations of Aedes aegypti and Ae. albopictus from six different regions in Cameroon to pesticides commonly used during military and civilian public health vector control operations. Methods Aedes mosquitoes were sampled as larvae or pupae between August 2020 and July 2021 in six locations across Cameroon and reared until the next generation, G1. Ae. aegypti and Ae. albopictus adults from G1 were tested following World Health Organization (WHO) recommendations and Ae. aegypti G0 adults screened with real time melting curve qPCR analyses to genotype the F1534C, V1016I and V410L Aedes kdr mutations. Piperonyl butoxide (PBO) assays and real time qPCR were carried out from some cytochrome p450 genes known to be involved in metabolic resistance. Statistical analyses were performed using Chi-square test and generalized linear models. Results Loss of susceptibility was observed to all insecticides tested. Mortality rates from tests with 0.25% permethrin varied from 24.27 to 85.89% in Ae. aegypti and from 17.35% to 68.08% in Ae. albopictus. Mortality rates for 0.03% deltamethrin were between 23.30% and 88.20% in Ae. aegypti and between 69.47 and 84.11% in Ae. albopictus. We found a moderate level of resistance against bendiocarb, with mortality rates ranging from 69.31% to 90.26% in Ae. aegypti and from 86.75 to 98.95% in Ae. albopictus. With PBO pre-exposure, we found partial or fully restored susceptibility to pyrethroids and bendiocarb. The genes Cyp9M6F88/87 and Cyp9J10 were overexpressed in Ae. aegypti populations from Douala sites resistant to permethrin and deltamethrin. Cyp6P12 was highly expressed in alphacypermethrin and permethrin resistant Ae. albopictus samples. F1534C and V1016I mutations were detected in A. aegypti mosquitoes and for the first time V410L was reported in Cameroon. Conclusions This study revealed that Ae. aegypti and Ae. albopictus are resistant to multiple insecticide classes with multiple resistance mechanisms implicated. These findings could guide insecticide use to control arbovirus vectors in Cameroon.